Problemy podgotovki fizkul'tutnykh kadrov v novykh sotsial'no-ekonomicheskikh usloviyakh reorganizatsii obshchestva - Blinov, V. M. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The author analyses some aspects on the professional training of physical culture specialists in Russia. Besides that, the author suggests several ways to improve the system of physical education as a whole.